Impacts of COVID-19 on Chinese nationals' tourism preferences - Huang, Songshan (Sam); Shao, Yuhong; Zeng, Ying; Liu, Xinyi; Li, Zhiyong (Tourism management perspectives, 2021)
This paper examines the impacts of COVID-19 on Chinese nationals' tourism preferences. Employing a mixed-method research design, two rounds of nation-wide online surveys were conducted, one in February 2020 when COVID-19 cases started to peak in China and another one in June 2020 when COVID-19 was a global pandemic; both survey studies were accompanied with semi-structured in-depth interviews and altogether 37 interviews were conducted in two stages. Based on both quantitative survey data and qualitative interview data, the research identified that: 1) COVID-19 significantly reduced Chinese nationals' preferences to travel to countries with high infection numbers, and geographically faraway, administratively and culturally distant outbound destinations; 2) Chinese nationals reduced their preferences in all travel modes and most of the tourism forms, but most of them would prefer nature-based, rural, and cultural destinations after COVID-19; and 3) shortened trips in short travel distance are preferred after COVID-19. The findings offer rich insights and practical implications for governments, industry organisations, and tourism operators to formulate tourism recovery strategies toward Chinese tourists. •This study examined the impacts of COVID-19 on Chinese nationals' tourism preferences.•Two rounds of nation-wide online surveys and semi-structured in-depth interviews were employed.•The findings yielded that COVID-19 had changed Chinese people's outbound destination preferences.•Chinese nationals preferred nature-based, rural, and cultural destinations after COVID-19.•Shortened trips in short travel distance were preferred after COVID-19.